The role of mind and innateness (fitrah) in proving the Islamic faith - Dawood, Mohammed Salman (International Journal of Psychosocial Rehabilitation, 2020)
Praise be to Allah the Lord of the worlds, and May the blessings and peace of Allah be upon the most honored of messengers our master Muhammad and all his family and companions: The belief in Allah is of great importance to the life of mankind, and what is all in this universe is devoted to mankind.